Carotenoid composition and sequestration in cassava (Manihot esculentum Crantz) roots - Drapal, Margit; Ovalle Rivera, Tatiana Melissa; Becerra Lopez Lavalle, Luis Augusto; Fraser, Paul D. (2024)
Cassava ( Manihot esculentum Crantz ) is a staple food source for many developing countries. Its edible roots are high in starch but lack micronutrients such as β-carotene. In the present study, analysis of pedigree breeding populations has led to the identification of cassava accessions with enhanced β-carotene contents up to 40 μg/g DW. This represents 0.2% of the Recommended Daily Allowance (RDA) for vitamin A. The β-branch of the carotenoid pathway predominates in cassava roots, with dominant levels of β-carotene followed by other minor epoxides of β-ring derived carotenoids. Metabolomic analysis revealed that steady state levels of intermediary metabolism were not altered by the formation of carotenoids, similar to starch and carbohydrate levels. Apocarotenoids appeared to be independent of their carotenoid precursors. Lipidomic analysis provided evidence of a significant positive correlation between carotenoid and lipid content, in particular plastid specific galactolipids. Proteomic analysis of isolated amyloplasts identified the majority of proteins associated with translation and carbohydrate/starch biosynthesis (e.g. glucose-1-phosphate adenylyltransferase). No carotenoid related proteins were detected even in the highest carotenoid containing lines. Carotenoids were associated with fractions typically annotated as plastoglobuli and plastid membranes (particularly the envelope). Proteomic analysis confirmed these structures apart from plastoglobuli, thus potentially amyloplast structures may not contain classical plastoglobuli structures.